Spiophanes norrisi sp. nov. (Polychaeta: Spionidae)a new species from the NE Pacific coast, separated from the Spiophanes bombyx complex based on both morphological and genetic studies - Meißner, Karin; Blank, Miriam (Zootaxa, 2009)
Morphological and genetic studies of specimens identified as Spiophanes bombyx (Claparède, 1870) revealed that the supposedly cosmopolitan species represents a species complex. Species belonging to this complex are S. bombyx (Claparède, 1870), S. aucklandicus Meißner, 2005, S. uschakowi Zachs, 1933 and the newly described S. norrisi. Morphological differences between these species are slight and concern the start of sabre chaetae, the shape of dorsal ciliated organs, and the start and number of neuropodial hooks in relation to body size. Specimens from the Atlantic Ocean examined in the course of this study also belong to this species complex but could not be assigned to any of the known species. Genetic differences between S. bombyx and S. norrisi in both examined genes (18S, COI) are significant and genetic distances are comparable to distances found between sister species in other spionid taxa. As expected, the nuclear 18S rRNA is generally more conserved than the mitochondrial COI gene. The significance beyond taxonomy of dorsal ciliated organs and of the presence of sabre chaetae in certain body regions is briefly discussed, but conclusions about the phylogenetic relationships and character evolution within Spiophanes must remain tentative.